Use of Optical Coherence Tomography to Detect Retinal Nerve Fiber Loss in Children With Optic Pathway Glioma - Zahavi, Alon; Toledano, Helen; Cohen, Rony; Sella, Sara; Luckman, Judith; Michowiz, Shalom; Goldenberg-Cohen, Nitza (Frontiers in Neurology, 2018)
Optic pathway glioma (OPG) presents in childhood and can cause significant morbidity and visual loss. Magnetic resonance imaging (MRI) is the current imaging modality of choice for evaluation of OPG progression, but it is a relatively limited resource often requiring sedation in the pediatric age group. Additionally, OPG progression on MRI does not always correlate with clinical progression. As a result, several other modalities for evaluating OPG are being investigated, including optical coherence tomography (OCT), a readily available imaging technique in ophthalmic practice. The purpose of the present study was to examine the association between retinal nerve fiber layer (RNFL) thickness measured using OCT and optic nerve function in children with OPG with and without neurofibromatosis-1 (NF-1). A retrospective chart review was conducted to identify children diagnosed with OPG from 2001 to 2015 at a tertiary pediatric medical center. The correlation between OCT measurements and clinical visual parameters was statistically analyzed. Included were 23 children with imaging-confirmed OPG and spectral domain OCT: 10 with NF-1 (mean age at diagnosis 5.8 years) and 13 without (mean age at diagnosis 5.9 years). The glioma involved the chiasma-hypothalamus in 19 patients, optic nerve in 11, and optic tract in 7; more than one anatomic site was affected in 15. Symptoms were reported in 2 patients with NF-1 and most patients without NF-1. Visual field defects included monocular, bitemporal, nasal, and homonymous hemianopia. Initial mean RNFL was 85.4 μm in the NF-1 group and 65 μm in the non-NF-1 group. Visual acuity deteriorated in 1/10 patients and 5/13 patients, respectively. Repeated OCT showed continued RNFL thinning in 3 patients (5 eyes) in the NF-1 group and in 8 patients (11 eyes) in the non-NF-1 group, often associated with a decrease in optic nerve function. In conclusion, visual function in children with OPG is correlated with repeated OCT measurements and weakly with neuroimaging. Children without NF-1 are usually symptomatic and have a worse clinical outcome. These findings may have important implications when considering initiating, continuing or stopping chemotherapy for OPG. The application of OCT in the assessment of OPG and the correlation of the findings to clinical progression can have a significant impact on OPG patient management.